Pattern of Maxillofacial Trauma among Patients with Head Injuries - Abul Hasnat; AKM Erfanul Hoque; Md Selim Ul Azam; Mohammad Kamrujjaman; Mahmuda Akhtar (Update Dental College, 2017)
Background: Patients with maxillofacial trauma are at high risk of having traumatic cranial injuries. Prompt determination of head injury in these patients is crucial for improving patients survival and smooth recovery. Objective: The purpose of this study was to find out the pattern of maxillofacial injuries in a patient with head injuries and to study their relationship. Study design: A prospective Cross-sectional descriptive study was made over 60 patients. Study setting and period: The study was conducted in the Department of Oral & Maxillofacial Surgery, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka-1000 from May 2010 to April 2011. Participants: Sixty patients with maxillofacial and head injuries were selected for the study. Methods: It was a prospective cross-sectional descriptive hospital based study. 60 patients who were diagnosed of having concomitant maxillofacial and head injuries were included in this study. Informations based on age, sex, mode of injury, pattern of facial and head injury, GCS score and type of head injury were taken for each case. Appropriate skull X-ray was done for all patients with maxillofacial injury and patients with initial sign of neurological deficit an initial CT scan of brain was done. Data was analyzed using the SPSS program. Results: Majority of the patients were in the 2nd to 4th decade (75%) with a male to female ratio of 7.57:1 Motor vehicle accidents were the most common cause of injury (60%), followed by fall from height (13.3%).- Mandible was the most commonly fractured facial bone (36.67%), followed by midface fracture (18.3%).Majority of the patients had moderate head injury and were managed conservatively. Among depressed fracture of skull, frontal bone was most commonly affected. Conclusion: Adult males were most common victims in craniofacial trauma, and road traffic accidents were responsible for the majority. Most of the patients sustained moderate head injuries and were managed conservatively. Open reduction and internal fixation with miniplates were used for displaced facial bone fractures. Update Dent. Coll. j: 2017; 7 (1): 14-20